Fetomaternal outcome in women with gestational diabetes mellitus - Fareed, Perveena; Siraj, Farhana; Lone, Kouser (International Journal of Research in Medical Sciences, 2017)
Objective: The aim of this study was to assess the fetomaternal outcome in patients with gestational diabetes mellitus. Methodology: This study was conducted in the department of obstetrics and gynecology GMC Srinagar. Patients with period of gestation more than 28 weeks with Gestational Diabetes Mellitus were included in study group and 100 non diabetic patients with similar period of gestation were taken as controls. Risk factors and fetomaternal outcome was compared in the two groups. Results: Gestational diabetes was seen commonly in patients with >30 years of age, increased parity, Positive family history and past poor obstetric history. Antepartum complications were seen more frequently in GDM group. Caesarean section rate was also high (74%) in diabetic group. Neonatal complications were seen more frequently in diabetic group. A significant percent (42.8%) patients developed overt diabetes over a one year follow up period. Conclusion: There was significant fetomaternal morbidity in patients with gestational diabetes mellitus. Hence early detection and treatment would reduce the fetomaternal mortality and morbidity.